Indonesian primary school teacher methods for the thematic learning of Kurikulum 2013: A case study - Rachman, Aditya (Indonesian Educational Administration and Leadership Journal (IDEAL), 2019)
In Indonesian context, the implementation of its new curriculum called Kurikulum 2013 (K-13) by primary school teachers was firstly begun in 2013. Thematic learning which is one of the compulsory parts for the teaching and learning processes becomes a great challenge especially for primary school teachers in the country. This case study was held in Banten, an Indonesian province aiming to understand kinds of teaching methods used by four Indonesian primary teachers in teaching to achieve thematic learning who voluntarily agreed to the study participants. Data collection was done using semi-structured interview with all participants while the data analysis was mainly conducted through thematic besides transcription and coding. The findings of the study informed four themes; teachers’ understanding of K-13, types of teaching methods used by the teachers, thematic integrated learning, the effectiveness of teaching and learning in the K-13. Recommendations were informed for all stakeholders (e.g. teachers, principals, and administrators) for the betterment of Indonesian education.